STUDY ON THE COMPOSITION AND CONTENT OF LIPIT IN VIETNAM CORAL - Ly, Dang Thi Phuong; Long, Pham Quoc; Hai, Ha Viet; Son, Nguyen Van; B., Imbs A. (Vietnam Journal of Marine Science and Technology, 2014)
Coral is an invaluable source in the medical and pharmaceutical industries, in which lipids play a role as a major nutrient reserves and the energy for coral. In this paper, we focus on researching the content and composition of lipid and fatty acids of 8 coral species from Vietnam. The total lipid of studied samples ranged from 10.1 to 20.4%; The content of essential polyunsaturated fatty acid (n-3), (n-6) dominated in both species contain zooxanthellae and not contain zooxanthellae. In 5 species that contain zooxanthellae, the polar lipid layer includes these following popular classes: PC, PE, PI, PS, LPC, LPE, LPS, DPG, CAEP. The total lipid content and composition, the different layers in total lipid and polar lipids were analized using TLC and image analysis program Sorbfil TLC Videodensitometer DV. The content and composition of fatty acids were also investigated using GC chromatography